Analisis Kebijakan Program Penguatan Pendidikan Karakter - Faturrahman, Faturrahman; Setiawan, Farid; Astuti, Windi Dwi; Khasanah, Khaliyatul (TSAQOFAH, 2022)
Character education is a wording of education and character. Where these two words represent the entire understanding of education and character combined, namely character education is a symbol of the nation's awareness of a character or moral crisis that occurs in society. Therefore, efforts are made to provide character education which is expected to be able to help people from a character crisis by incorporating character education into the current education system through educational institutions. Several methods and research are carried out in order to achieve an appropriate approach to the success of the character education program. The need for each individual to be aware of the importance of character development in each of them is the main key to strengthening character, which can be done from the deepest outward levels, namely self, family, community, school, organization, to a wider scope, namely the Indonesian nation.